TINGKAT KEPATUHAN DAN KETERSAMPAIAN INFORMASI SPT PADA GURU DAN KARYAWAN SEKOLAH DI BOGOR: Level of Compliance and Delivery of SPT Information to Teachers and School Employees in Bogor - Mela Nurdialy; Aulia Hidayati; Novi Rosyanti; Ratih Pratiwi; Eka Merdekawati (IPB University, 2022)
Principals, teachers, treasurers, and school employees in Bogor city are individual taxpayers (WP OP). Compliant taxpayers report income and tax payments following applicable laws. WP OP should report the annual personal income tax return (SPT) electronically using e-SPT or e-filing.The Directorate General of Taxes (DGT) has published and socialized SPT reporting and provided an online DGT website to facilitate annual SPT reporting.The purpose of this study was to determine the level of compliance with tax payments and reporting of Annual PPh WP OP SPT and the level of electronic submission of Annual PPh SPT filling and delivery information to school managers (principals, teachers, treasurers, and school employees) in the city of Bogor.This descriptive qualitative research uses primary data using a survey method by distributing questionnaires with a simple random sampling to teacher respondents, principals, treasurers, and school employees in Bogor city.Most of the respondents (90%) comply with their obligations as taxpayers. All respondents considered training to fill out SPT useful, but 66% had difficulty getting information regarding procedures for filling out SPT, and 96% of respondents felt that DGT rarely held training for filling out e-SPT. Most respondents know SPT reporting information from friends, superiors, family, and office. DGT must increase the number, materials, and publication media and socialize filling out the Annual SPT to the public. ABSTRAKKepala sekolah, guru, bendahara dan karyawan sekolah di kota Bogor merupakan wajib pajak orang pribadi (WP OP). Wajib pajak yang patuh melakukan pelaporan penghasilan dan pembayaran pajak sesuai dengan undang-undang yang berlaku. WP OP sebaiknya melaporkan Surat Pemberitahuan (SPT) tahunan Pajak Penghasilan orang pribadi secara elektronik menggunakan e SPT atau e-filing.Direktorat Jenderal Pajak (DJP) telah melakukan publikasi dan sosialisasi pelaporan SPT serta menyediakan website DJP online untuk memfasilitasi pelaporan SPT Tahunan.Tujuan penelitian ini untuk mengetahui tingkat kepatuhan pembayaran pajak dan pelaporan SPT Tahunan PPh WP OP serta tingkat ketersampaian informasi pengisian dan pelaporan SPT Tahunan PPh secara elektronik pada pengelola sekolah (kepala sekolah, guru, bendahara dan karyawan sekolah) di kota Bogor.Penelitian ini termasuk jenis penelitian kualitatif deskriptif yang menggunakan data primer dengan menggunakan metode survey melalui penyebaran kuesioner dengan teknik pengambilan sampel menggunakan simple random sampling kepada responden guru, kepala sekolah, bendahara dan karyawan sekolah di kota Bogor.Sebagian besar responden (90%) patuh melaksanakan kewajibannya sebagai Wajib Pajak. Seluruh responden menganggap pelatihan pengisian SPT bermanfaat namun 66% responden kesulitan untuk mendapatkan informasi mengenai tatacara pengisian SPT dan 96% responden merasa DJP jarang mengadakan pelatihan pengisian e-SPT. Kebanyakan responden mengetahui informasi pelaporan SPT dari teman, atasan, keluarga dan kantor. DJP harus meningkatkan jumlah, materi, dan media publikasi dan sosialisasi pengisian SPT Tahunan kepada masyarakat.